Eco-Jurisprudence on Deforestation-Induced Disasters: Establishing a Legal Nexus Between Forest Clearance and Environmental Crimes - Emirza Henderlan Harahap (International Journal of Science and Environment (IJSE), 2026)
The escalating frequency of deforestation-induced disasters in the Anthropocene has exposed a significant gap in global ecological governance, where scientific causality often fails to translate into judicial liability. This research explores the integration of eco-jurisprudence and forensic ecology to establish a robust legal nexus between forest clearance and environmental crimes. Using a normative juridical methodology supported by a comparative legal approach, the study analyzes how hydrological modeling and spatial data can be transformed into admissible legal evidence. The results demonstrate that by utilizing the "Causality-Nexus Protocol," the judiciary can apply the doctrine of strict liability for environmental negligence, bypassing the traditional hurdles of proving subjective intent (mens rea). By citing international human rights standards and recent advancements in attribution science (2021–2025), the study argues that catastrophic floods and landslides resulting from canopy loss constitute a violation of the non-derogable right to life. The novelty of this research lies in the conceptualization of the ecosystem as a "silent witness," providing a standardized framework for "Scientific Jurisprudence." This paper concludes that establishing a definitive legal nexus is essential for shifting environmental law from reactive administrative oversight to proactive criminal accountability, thereby strengthening global ecological governance.